2020
DOI: 10.1016/s2352-3018(20)30105-3
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining HIV care during the COVID-19 pandemic

Abstract: Can population differences explain the contrasting results of the Mwanza, Rakai, and Masaka HIV/ sexually transmitted disease intervention trials? A modeling study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
270
0
23

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 292 publications
(296 citation statements)
references
References 4 publications
3
270
0
23
Order By: Relevance
“…While there are many obvious challenges to EDs during the pandemic, there are also possible opportunities to reach patients who otherwise would not have sought care. Maintaining high levels of routine HIV screening in the ED is crucial, as other community-based organizations and health clinics may have ceased to offer in-person evaluations and HIV screening, making it even more difficult to be tested for HIV during the COVID-19 pandemic [6,7].…”
Section: Lessons Learnedmentioning
confidence: 99%
“…While there are many obvious challenges to EDs during the pandemic, there are also possible opportunities to reach patients who otherwise would not have sought care. Maintaining high levels of routine HIV screening in the ED is crucial, as other community-based organizations and health clinics may have ceased to offer in-person evaluations and HIV screening, making it even more difficult to be tested for HIV during the COVID-19 pandemic [6,7].…”
Section: Lessons Learnedmentioning
confidence: 99%
“…These social controls can hinder or delay PLWH's access to HIV care and support at hospital or clinic sites. For instance, a study conducted in China found that 32.6% of PLWHs were at risk of discontinuing ART and about 48.6% did not know where to get needed medications due to COVID-19 lockdown measures [4]. In SSA, the effect of travel restrictions on PLWHs could be even more detrimental given the long distances they must often travel to access treatment and care due to the limited availability of specialized HIV services, preferences for higher-tiered facilities, and efforts to mitigate social stigma surrounding treatment [10,11].…”
Section: Impeding Access To Clinical Carementioning
confidence: 99%
“…In SSA, most PLWHs receive treatment and care from poorly resourced public health facilities with inadequate infrastructure and staff shortages [17,18]. Even in well-resourced treatment contexts (e.g., China), evidence suggests that many PLWHs cannot access their ART medication or face delays in treatment because hospitals are busy treating patients with COVID-19 [4]. Given that most public health facilities in SSA struggled to provide HIV treatment and care before the COVID-19 pandemic, significant numbers of PLWHs will likely face service disruptions unless timely, intentional steps are taken to prevent them.…”
Section: Overburdening Public Health Providersmentioning
confidence: 99%
“…Insights depicted about decrement in HIV testing which is the stepping stone for HIV care. This is affected due to lockdown, quarantine and social distancing, hampering UNAIDS' first 90-90-90 target at a global sphere which states how 90% HIV-positive patients will be verified about their HIV status [36].…”
Section: Hivmentioning
confidence: 99%